Chylous ascites after complete mesocolic excision for right‐sided colon cancer with D3 lymphadenectomy: A retrospective cohort‐study. (22nd December 2021) - Sun, Yanwu; Deng, Yu; Lin, Yu; Lin, Huiming; Huang, Ying; Jiang, Weizhong; Chi, Pan
Abstract: Aim: This retrospective study was designed to evaluate risk factors of the occurrence and severity of chylous ascites after complete mesocolic excision (CME) and D3 lymphadenectomy in patients with right‐sided colon cancer. Methods: Consecutive patients receiving CME and D3 lymphadenectomy for right‐sided colon cancer were included. Risk factors of the occurrence and severity of chylous ascites by using logistic analysis were assessed. A nomogram predicting chylous ascites was constructed. Results: Among 661 patients included in the study, postoperative chylous ascites occurred in 48 (7.3%) patients. Logistic regression analysis demonstrated that prognostic nutritional index (PNI ≤ 47, OR = 2.172, p = 0.016), laparoscopic surgery (OR = 2.798, p = 0.034), operating time (>225 min, OR = 2.645, p = 0.002), and apical lymph node (APN) metastasis (OR = 3.698, p = 0.034) were correlated with the occurrence of postoperative chylous ascites. A nomogram predicting postoperative chylous ascites was constructed (C‐index 0.701). 31.2% (15/48) of patients with chylous ascites were resolved in more than 7 days. The number of retrieved lymph nodes (OR = 1.074, 95% CI: 1.002–1.152, p = 0.044) and PNI ≤ 47 (OR = 7.890, 95% CI: 1.224–50.869, p = 0.030) were independently predictive of prolonged chylous ascites resolution (≥7 days). Conclusions: In our series, 7.3% of patients developed chylous ascites after right hemicolectomy with CME and D3 lymphadenectomy. Laparoscopic surgery, PNI, operation time, and APN metastasis were independently predictive of postoperative chylous ascites. Lower PNI and more retrieved lymph nodes were correlated with prolonged resolution of chylous ascites.